Angola : Fifth Review Under the Stand-By Arrangement, Request for Waiver of Applicability of Performance Criteria, and Request for Modification of Performance Criteria: Staff Report; Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Angola. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The Executive Board of the IMF has completed the fifth review of Angola's economic performance under a program supported by the Stand-By Arrangement. The Board's decision enables the immediate disbursement of an amount equal to SDR 85.9 million, bringing total disbursements under the arrangement with Angola to an amount equal to SDR 773.01 million. The Angolan authorities should be commended for strong performance under the IMF-supported stabilization and reform program. The sustained fiscal adjustment, helped by higher oil prices, has fostered reserve accumulation, a stable exchange rate, and declining inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet